Modelling of GaAs Charge Sensitive Amplifiers - Navickas, R.; Barzdėnas, V. (Elektronika ir Elektrotechnika, 2005)
GaAs integrated circuit the charge sensitive amplifier (CSA) is generally used for pixel detectors in mammography and dentography. Computer simulation was carried out by ORCAD-PSPICE simulator. The amplifier has bipolar response with peaking time about 8,5 ns and 39.4 mV/fC gain, equivalent noise charge of input ENC=184 ē rms and low power consumption is 0.94 mW when input charge is 20 fC, load resistance – 1 MΩ and the capacitance - 2,5 pF. Ill. 11, bibl. 6 (in Lithuanian; summaries in Lithuanian, English and Russian).